The Free Trade Zone Policy : A Pathway to the Development of a Special Economic Zone in Batam City - Betric Hasibuan; Lubna Salsabila; Timbul Dompak (International Journal of Social Welfare and Family Law, 2025)
Batam City is a national strategic area that has played a significant role in Indonesia's economic growth since the 1970s. Through its Free Trade Zone (FTZ) policy, Batam has successfully attracted significant investment and developed into an export-oriented trading center. However, the implementation of regional autonomy has created institutional dualism between the Batam City Government and the Batam Business Entity (BP Batam), resulting in overlapping authority, regulatory uncertainty, and a decline in regional economic competitiveness. This study aims to analyze regional development policy strategies that align with the vision of the Batam City Long-Term Regional Development Plan (RPJPD) 2025–2045. This study uses a descriptive qualitative approach with data collection techniques through document studies, secondary data, and interviews with key stakeholders. The results indicate that institutional restructuring is an urgent need to eliminate overlapping authority between the central and regional governments. In addition, harmonization of central and regional regulations, strengthening infrastructure, and improving the quality of human resources are strategic steps in Batam's transition from an FTZ to a Special Economic Zone (KEK). To achieve Batam's successful development in the future, inclusive multi-stakeholder collaboration and governance that adapts to global dynamics are needed. A policy strategy based on synergy, regulatory efficiency, and resource readiness is believed to be able to support the achievement of sustainable economic transformation in accordance with the region's long-term vision.